Announcing mandatory submission of PDBx/mmCIF format files for crystallographic depositions to the Protein Data Bank (PDB). Issue 4 (16th April 2019) - Adams, Paul D.; Afonine, Pavel V.; Baskaran, Kumaran; Berman, Helen M.; Berrisford, John; Bricogne, Gerard; Brown, David G.; Burley, Stephen K.; Chen, Minyu; Feng, Zukang; Flensburg, Claus; Gutmanas, Aleksandras; et al.
Abstract : This letter announces that PDBx/mmCIF format files will become mandatory for crystallographic depositions to the Protein Data Bank (PDB). Abstract : This letter announces that PDBx/mmCIF format files will become mandatory for crystallographic depositions to the Protein Data Bank (PDB).